Childhood acute lymphoblastic leukemia in Mexico: mortality trend analysis, 1998-2018 - Paloma Muñoz-Aguirre; Marta Zapata-Tarrés; Priscilla Espinosa-Tamez; Hugo Sánchez-Blas; Marion Brochier; Héctor Lamadrid-Figueroa (Salud Pública de México, 2022)
Objective. To determine the magnitude of mortality due to acute lymphoblastic leukemia (ALL) nationally and by age group, sex, state of residence and insurance status, as well as to evaluate time trends during the period 1998-2018 Materials and methods. We obtained ALL mortality data and estimated age-standardized national, state-level and health insurance mortality rates. We conducted a joinpoint regression analysis to describe mortality trends across the study period and estimate the average annual percent change (AAPC). Results. In a 20-year period, age-standardized ALL mortality rates increased from 1.6 per 100 000 in 1998 to 1.7 in 2018. Nationally, a constant annual increase in mortality was observed for both sexes (1998-2002 AAPC 0.6 in boys, and 1998-2002 AAPC 0.3 in girls). We observed heterogeneity in childhood ALL at a state level. Conclusion. Our results reflect the social, economic, geographic diversity of the country. Monitoring and surveillance of this disease is crucial to assess quality of care.